Geografi dan perdagangan: kepentingan Selat Melaka kepada perdagangan dunia, Asia dan dunia Melayu 1700-1800 - Nordin Hussin, (Universiti Kebangsaan Malaysia, 2008)
This article is an attempt to analyse the strategic geographical location of the Straits of Melaka, which was used by seafarers and traders travelling from the East and the West. The strategic position of the Straits of Melaka controlling the movement of the world trade in the East, which is rich in mineral resources, and its strategic location between China and mainland India was known since the Srivijaya era. Subsequently this strength was fully utilised by the Malay kingdom in Melaka, the Achenese in Sumatra and the Johor kingdom in Riau. Nevertheless, the strategic position of the port of Melaka and Riau that controlled the world trade finally led to their downfall when both port towns were occupied by the three European powers (Riau was occupied by the Dutch after the 1784 war). The significant role of the Straits of Melaka also became a dispute factor between the three European powers (Portugese, Dutch and English). Thus, whichever power succeeded in controlling the Straits of Melaka, it would be the one that hold the power to regulate the movement of the world trade, which was a lucrative and profitable business.